Trust-politik Korea Selatan kepada Korea Utara dalam Konteks Reunifikasi Korea Pada Pemerintahan Park Geun-hye - Esty Fidhela Muliawati; Widya Setiabudi; Wawan Darmawan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The reunification of Korea is something that has been continuously discussed in every government of the presidents of South Korea. The concept of foreign policy of the 11th President of South Korea, Park Geun-hye, is known as Trust-Politics Policy. Trust-politics is President Park's overarching political philosophy. It is a vision and a policy tool applied to domestic politics and international relations. At its heart lies the concept of trust. Trust-Political Policy, influenced by internal and external factors. This politics seeks to build mutually binding expectations based on global norms. The purpose of the problem in this research is to find out the idea of reunification of South and North Korea during President Park and to explain South Korea's Trust-Political Policy to North Korea in the context of Korean Reunification. Researchers used qualitative research methods with literature study techniques in the process of collecting data. Based on the results of discussion and data analysis, reunification can be carried out using three Korean reunification scenarios, namely unification through evolution and adaptation systems, unification through collapse and absorption, and unification through conflict. As well as the idiosyncratic factors that influence Park in politics are factors of leadership, belief, culture, and the political system.